The Lived Religion of Bereaved Parent of Human Trafficking Victims in East Nusa Tenggara - Liliya Wetangterah (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2022)
Human Trafficking has an impact on various aspects of life. One of them is the experience of parents who have to lose their daughters as victims of human trafficking. Living in meaningful life after losing a loved child is challenging. The objective of this study is to explore the experience of bereaved parents particular, the parent who loses a beloved daughter who works away from home as a domestic worker. This research interviewed four participants (two couple of parents) of deceased victims of human trafficking in East Nusa Tenggara-Indonesia. The bereaved experience challenges their perspective on life, the human limitation, and the assumption about justice. Religion assists the parent in coping and meaning to deal with the bereaved experience. Related to the sense of control,  the bereaved parent perceives the same meaning of the Divine plan but in the term of justice, the bereaved parent has a different perspective that obtains a different outcome. A beloved parent passively surrenders to God's revenge while the other bereaved parent understands justice involves forgiveness also law enforcement of perpetrators.